Sex Ratio at Birth: Where Did Our Female Fetus Go? - Gurung, T K; Gurung, R T; Shrestha, R; Shrestha, R (Journal of Gandaki Medical College-Nepal, 2018)
Objectives: The aim of the study was to determine the ratio of male to female gender at birth and compare the sex ratio between primipara and multipara women. Methods: This is a cross sectional retrospective study done using the data available from the medical records of the patients who were admitted in the labor room of Gandaki Medical College Teaching Hospital from July 2016 to June 2017 (Shrawan 2073 to Asad 2074). Results: In one year period, a total of 1625 women were admitted for delivery. There were 845 male and 780 female babies delivered to those women. The sex ratio calculated was 108 male births for every 100 females. When comparing the sex ratios at birth for primipara, multipara with previous abortions and fetal death and mulipara with no history of abortions and fetal death, the sex ratio was 81.75, 125.89 and 120.16 respectively. Conclusions: Overall there were more male births than female. But in primiparous women more female babies were born unlike in multipara. There is definitely a need of in depth study to identify the cause for the skewed value. The society needs to acknowledge that high sex ratios at birth will adversely affect the fertility patterns causing the imbalance in the overall development of community. J-GMC-N | Volume 11 | Issue 01 | January-June 2018, Page: 1-4